The Social and Economic Impact of Sanctions and Time Limits on Recipients of Temporary Assistance to Needy Families - Lindhorst, Taryn (2006)
A central feature of the reforms enacted through the Personal Responsibility and Work Opportunity Reconciliation Act (welfare reform) has been the adoption of strategies to involuntarily remove Temporary Assistance to Needy Families (TANF) recipients from the welfare rolls, including increased use of sanctions and time limits on welfare receipt. Drawing on data from a three year panel study of women who had been receiving welfare in a state which adopted stringent sanctioning and time limit policies, we investigate predictors of recipients’ TANF status after implementation of welfare reform, and identify differences in post-reform material resources, hardships and quality of life based on TANF status. Almost half of all welfare case closures during the first time period after reforms were implemented through involuntary strategies. Relatively few baseline characteristics predicted different outcomes once welfare time limits and sanctions were implemented. Those who were timed off welfare had substantially lower incomes in the year following their removal. One third of all respondents, regardless of reason for leaving TANF reported having insufficient food, housing problems and lack of access to needed medical care.